An autoregressive distributive lag for the analysis of macroeconomic variables on stock market returns in Nigeria - Ali, Umar Ahmad; Abdullah, Adam; Sulong, Zunaidah; Ahmad, TIjjani Abdullahi (AENSI, 2015)
This study provide an empirical investigation on the relationship between the stock market returns and macroeconomic variables in order to enhance the ability of economic agents in the analysis of stock market performance in Nigeria using Autoregressive Distributive Lag (ARDL). Annual time series data of six variables namely; broad money supply, nominal effective exchange rate, short term treasury bills rate, foreign direct investment, gross domestic per capita income, and gross domestic saving from 1984-2013 were employed to analyse the existence of short-run and long-run relationship between the selected macroeconomic variables and stock market returns. The results from the Augmented Dickey-Fuller and Phillips-Perron tests of stationarity indicated that all the variables were non-stationary at level I (0) and were stationary at first difference I (1). The Bound test procedure also revealed that the stock market returns and the macroeconomic variables were cointegrated and, thus, a long-run equilibrium relationship exists between them. Likewise, the Granger causality tests showed that some of the macroeconomic variables were having bidirectional causality with the stock market returns; while others have unidirectional causality. As a result, Policy makers, financial institutions and private investors need to take the macroeconomic indicators into consideration when formulating financial and economic policies, diversification strategies and restructuring of the portfolios.